Pembelajaran Berbantuan Proyek Menggunakan Software CompliCalc terhadap Kemampuan Berpikir Komputasi pada Siswa - Annisa Ul Khoiriah Pasaribu; Yahfizham Yahfizham (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The objective of this study is to examine the effect of project-based learning facilitated by CompliCalc software on the computational thinking skills pertaining to middle school students. Using a quasi-experimental design, Two student groups were involved in the study: the experimental group and the control group. The results revealed that the use of CompliCalc significantly improved computational thinking skills. The data also showed students' active involvement in logical and systematic thinking through projects. This study recommends the integration of educational software in project-based learning activities.